Factors affecting medical tourism: A case study of Azeri tourists in Iran - Shafizadeh, Kiarash; Hezari, Navid; Sohrabi, Mohammad-Reza (Social Determinants of Health, 2020)
Background: Health tourism is one of the effective factors in the economic prosperity of the countries, the beautiful nature and hot springs of Ardebil province makes it a good destination for health tourism. The aim of this study was to investigate demographic and socioeconomic characteristics of health tourists in Ardebil. Methods: To investigate the viewpoint of health tourists coming to Ardebil province from Azerbaijan, a comprehensive Turkish language questionnaire was designed by the researcher and by visiting medical centers in Ardebil, pharmacies and restaurants, the questionnaires were completed. Results: Out of 200 distributed questionnaires, 193 were completed. The average age of the participants was 26.2 years. They often had less than 1800 USD monthly income. 184 (95.4%) of participants were not covered by the general insurance of Azerbaijan. The cost of treatment and the total travel cost per person for participants was less than 120 USD. About the hospital services, one-third of respondents rated them as “well”. More than 95% of the tourist were from the near border provinces. Conclusion: The lack of public insurance coverage in Azerbaijan and the higher value of the Azerbaijani Manat compared to Iranian rial attract health tourists to Ardebil, but the quality of services provided needs to be improved. Government planners need to focus more on health tourism issues, especially in Ardebil so as to improve the infrastructures and remove barriers, it is a step towards the prosperity of this lucrative industry.